(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2026)
This paper seeks to analyze the pictorial work of contemporary American visual artist James Mertke, focusing on two of his still lifes: Paper Airplane (2023) and Disco Ball (2022). To this end, the research takes the form of a philosophical essay as well as a paradigmatic case. Based on a brief historiographical account of the genre and the postulates of the German philosopher Peter Sloterdijk, it concludes that the style, the predominant aesthetic thought, and the lines of the art of the future with which the painting of this Californian artist, USA, could coincide are, respectively, playful and ornamental realism. This understands, on the one hand, the ideas of playful performance of the object and the imitation of decoration without apocalyptic haste and, on the other, something more characteristic of craft enthusiasts and preferably neonaive. The fundamental metaphor of the essay is the following: Still Life as Anatomy of Matter.